Transposable Prophage Mu Is Organized as a Stable Chromosomal Domain of E. coli - Saha, Rudra P. (Public Library of Science, 2013)

(untitled)
The E. coli chromosome is compacted by segregation into 400–500 supercoiled domains by both active and passive mechanisms, for example, transcription and DNA-protein association. We find that prophage Mu is organized as a stable domain bounded by the proximal location of Mu termini L and R, which are 37 kbp apart on the Mu genome. Formation/maintenance of the Mu ‘domain’ configuration, reported by Cre-loxP recombination and 3C (chromosome conformation capture), is dependent on a strong gyrase site (SGS) at the center of Mu, the Mu L end and MuB protein, and the E. coli nucleoid proteins IHF, Fis and HU. The Mu domain was observed at two different chromosomal locations tested. By contrast, prophage λ does not form an independent domain. The establishment/maintenance of the Mu domain was promoted by low-level transcription from two phage promoters, one of which was domain dependent. We propose that the domain confers transposition readiness to Mu by fostering topological requirements of the reaction and the proximity of Mu ends. The potential benefits to the host cell from a subset of proteins expressed by the prophage may in turn help its long-term stability.